Effects of physical exercise on cancer patients: a systematic review - Buchman, Małgorzata; Kiersznowska, Nina; Bogacka, Anna; Górowska, Anna; Sobiś , Martyna; Janik, Natalia; Janowiak, Julia; Wadowska, Zuzanna; Lenart, Julia; Miłek, Barbara (Quality in Sport, 2025)
Background: Cancer and its treatments frequently lead to substantial declines in physical function, cardiorespiratory fitness, muscle strength, and overall quality of life. Common symptoms such as fatigue, reduced mobility, and psychological distress can persist long after treatment completion, underscoring the need for supportive interventions that address the broader physical and psychosocial burden of cancer. Over recent decades, physical exercise has become a staple of supportive oncology, with growing evidence demonstrating its ability to mitigate treatment-related side effects, preserve functional capacity, and enhance well-being across the cancer care continuum. Aim: Evaluation and emphasis of the effects of physical exercise on physical, clinical, and patient-reported outcomes in adults with cancer. Specifically, this review synthesizes evidence across different exercise modalities, cancer types, and treatment phases to determine the overall benefits, safety, and feasibility of exercise in oncology care. Material and methods: A systematic review of selected literature was conducted using the PubMed and open-access databases, using keywords such as: exercise*, physical* activity*, cancer*. This review includes a mix of randomized controlled trials, pilot and feasibility studies, prospective cohort studies, cross-sectional studies, and mechanistic systematic reviews. The analysis focused on peer-reviewed articles published between 2010 and 2024. Results and conclusions: Across cancer types and treatment phases, structured exercise consistently improved fitness, reduced fatigue, and enhanced quality of life. Prehabilitation improved preoperative capacity and reduced complications in upper-GI cancers. Exercise was safe and feasible, including in metastatic populations, and mechanistic evidence showed reductions in inflammatory markers. Overall, the evidence supports exercise as an effective, low-risk supportive therapy that enhances functional outcomes and should be integrated into routine oncology care.